A simplified method for evaluating singular stress field and fatigue strength of U-shaped notch. (July 2020) - Shen, Wei; Qiu, Yu; Yan, RenJun; Xu, Linzhi; Liu, Enqian
Abstract: In order to simplify the assessment method of notch stress and fatigue strength for cruciform welded structures in ocean engineering, a simple stress assessment formula based on singular strength values a s i and b s i was presented according to linear elastic fracture mechanics and notch stress strength theory. In view of the stress singularity caused by the V-notch, the stress of the corresponding U-notch was recommended and used for fatigue evaluation. Therefore, on the basis of V-notch stress formula, a simplified U-notch stress field evaluation formula was obtained by theoretical analysis and numerical calculation. After a series of verification, it is found that the stress distribution and fatigue strength evaluation formula for cruciform welded joints based on singular strength values proposed in this paper can simply and accurately predict the notch stress at welded joints. The result of fatigue strength evaluated by the simplified formula has a smaller scatter band. Highlights: Singular strength values a s i and b s i are proposed to describe stress singularity effects. A theoretical and fitting formula for predicting V-shaped and U-shaped notches. Considering different virtual radii, the simple formula for notch stress is used to evaluate fatigue strength.